Quand un tiers-lieu devient multiple. Chronique d’une hybridation - Martine Azam; Nathalie Chauvac; Laurence Cloutier (Recherches Sociologiques et Anthropologiques, 2015)
This article focuses its attention on the emergence of a Toulousan third space called “Le Multiple”. Its story is told here in three stages : the encounter between two “worlds” – a fab lab and a project fostering social and solidary economy, engagement in a common space, and the structuring of activities and group projects. Based on interviews and in situ observations, our analysis is centred on the interactions founding the group action. Situated in the inter-actionist current, our procedure takes the key-role played by the space into account, sometimes a pretext, sometimes a motor, sometimes a catalyst, which, given events creating major reorientations and potential irreversibilities, engaged the various participants in ways they had not necessarily foreseen.